2021
DOI: 10.1097/md.0000000000026780
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 effect-site concentrations of remifentanil with midazolam during percutaneous transluminal balloon angioplasty under monitored anesthesia care

Abstract: Background:Until now, target-controlled infusion of remifentanil with midazolam in percutaneous transluminal balloon angioplasty for dysfunctional hemodialysis fistulas has not been described. Here, we investigate 2 effect-site concentrations of remifentanil with intermittent bolus midazolam for percutaneous transluminal balloon angioplasty under monitored anesthesia care.Methods:A prospective, randomized controlled trial including patients who received a percutaneous transluminal balloon angioplasty between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Here, we first reported that REMI Ce of 2.0 µg/mL by TCI pump with 3 to 4 mg midazolam and intrarectal lidocaine gel use provided adequate analgesia and sedation, appropriate hemodynamic conditions, acceptable adverse events (apnea with desaturation; SpO 2 88%-89%), and better surgeon satisfaction in TRUS-guided prostate biopsy under PAS as our previous research in percutaneous transluminal balloon angioplasty for dysfunctional hemodialysis fistulas. [10] Anesthesia for TRUS-guided prostate biopsy should be quick in onset of action, have an easily reversible effect, and result in minimal adverse effects while allowing the procedure to be performed on an outpatient basis. The Urological Society of Australia and New Zealand prostate biopsy survey in 2013 showed that 57% of urologists used PAS or general anesthesia, 28% periprostatic nerve block (PNB), and 4% no analgesic agent.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we first reported that REMI Ce of 2.0 µg/mL by TCI pump with 3 to 4 mg midazolam and intrarectal lidocaine gel use provided adequate analgesia and sedation, appropriate hemodynamic conditions, acceptable adverse events (apnea with desaturation; SpO 2 88%-89%), and better surgeon satisfaction in TRUS-guided prostate biopsy under PAS as our previous research in percutaneous transluminal balloon angioplasty for dysfunctional hemodialysis fistulas. [10] Anesthesia for TRUS-guided prostate biopsy should be quick in onset of action, have an easily reversible effect, and result in minimal adverse effects while allowing the procedure to be performed on an outpatient basis. The Urological Society of Australia and New Zealand prostate biopsy survey in 2013 showed that 57% of urologists used PAS or general anesthesia, 28% periprostatic nerve block (PNB), and 4% no analgesic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we first reported that REMI Ce of 2.0 µg/mL by TCI pump with 3 to 4 mg midazolam and intrarectal lidocaine gel use provided adequate analgesia and sedation, appropriate hemodynamic conditions, acceptable adverse events (apnea with desaturation; SpO 2 88%–89%), and better surgeon satisfaction in TRUS-guided prostate biopsy under PAS as our previous research in percutaneous transluminal balloon angioplasty for dysfunctional hemodialysis fistulas. [10]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations